Acerca de la institucionalización de la psicología como profesión en el Perú y de un aspecto de su devenir como disciplina científica - Lerner Stein, Roberto (1991)
The author tries to present the facts that preceded the law that created- in 1980- the Peruvian Psychological Association, analizing the academical and professional representativity that existed before in the Peruvian Psychological Society. Also some explanations are given about the dicotomies  objective-intuitive and spoken-writen in response to a paper from León that appears in this number.